O direito fundamental ao trabalho da pessoa com deficiência no Brasil : caminhos para a eficácia social - Resende, Emerson Albuquerque (2016)
This study analyzes rules of law on the right to work of the person with disabilities in Brazil. It should be a reflection on the practical implications of the ratification by Brazil of international standards that address the human rights of people with disabilities, especially the International Convention on the Rights of Persons with Disabilities, which brought important fundamental rights such as the right to work, accessibility, reasonable accommodation, autonomy and independence, among others, in addition to a concept of a person with disabilities with a focus on barriers by establishing the social model of disability. Evaluates the consequences of the constitutional rule, including the recent Brazilian Law of Inclusion, always looking up to maximum effectiveness of the constitutional norm. Searching to materialize the right to work, the Brazilian legislation adopts mainly two models: the repressor, which prohibits discriminatory practices, and affirmative action including reservation of jobs in private companies and reservation of public offices and positions. With support on statistical data and information from the Brazilian Government and from companies included in the list of Best of Magazine Exame of 2014, it is observed that in practice, even twenty-four years after the rule of law that established such system in the private sector, much work of the various actors involved are to be made to the reservation of vacancies in companies is effectively enforced. Similarly, with the data analysis of the key public enterprises and joint capital companies, it was found that, if they continue at the pace it is, reserve positions and jobs, as laid down in the Constitution, it will take more than a century to happen. Following this path, of case studies, it became evident that affirmative action has a lot to be improved and that the repressive model barely got off the ground. Therefore, before the inefficiency of the standard, if making comparisons with the experiences of other countries, various proposals are presented in enhancing the prospect of national legislation, public policies and business practices, such as improvement of legal instruments, including small and medium companies in the process of tax incentive programs, affirmative action training and education, improvement of the statistical system, development of combat mechanics to indirect discrimination, strengthening the safety net, developing strategies for job security, creating lists of companies non-complying quota, demanding quotas for participation in tenders and the improvement of the performance of public protection agencies, among others, that will lead to greater social effectiveness of this important fundamental right.